(untitled) (KULT_online, 2022)
The monograph Ohnmacht in der Demokratie is a sociological evaluation of an empirical survey of qualitative interviews conducted for the project “Willkommenskultur und Demokratie in Deutschland” that examines participation in democratic processes in the Federal Republic of Germany. The author, Nikolai Huke, focuses primarily on the individual’s (in)ability to shape his or her own life and to participate in political processes as well as on structural causes such as political exclusion and overwhelm.